Agricultural Modernization and Social Change in Farming Communities in Arokke Hamlet, Lili Riattang Village, Lappariaja District, Bone Regency - Dandi; Andi Agustang; A. Octamata Tenri Awaru (HISTORICAL: Journal of History and Social Sciences, 2023)
This research aims to (1) describe agricultural modernization in farming communities in Arokke Hamlet, Lili Riattang Village, Lappariaja District, Bone Regency. (2) to describe the impact of agricultural modernization on social changes in farming communities in Arokke Hamlet, Lili Riattang Village, Lappariaja District, Bone Regency. This research uses descriptive qualitative research methods. The data collection process carried out was (1) Observation (2) Interview (3) Documentation. To more easily understand the events being studied, the author uses Talcot Parsons' Functionalism theory approach. The research results show that (1) The development of agricultural modernization in the farming community in Arokke Hamlet, Liliriattang Village is a change in agricultural procedures from traditional to more advanced or modern. Agricultural modernization itself is considered more practical, faster, and makes it easier for farmers to cultivate agricultural land from the process of cultivating rice fields to the harvesting stage. The modernization of agricultural farming in the farming community in Arokke Hamlet, Liliriattang Village is: (a) the values of modernization are the attitude of openness of the farming community towards the changes that occur. (b) agricultural organizations, namely the formation of farmer groups. (c) agricultural technology, based on research results, a form of modernization in agricultural technology is the use of agricultural tools with advanced technology. (d) community knowledge in the use of agricultural technology, agricultural modernization has good potential and opportunities for progress in the agricultural sector, but this potential must be accompanied by knowledge about agricultural modernization so that people are able to manage their agriculture well so that it has an impact on maximum final results. (2) The impact of agricultural modernization on social changes in the farming community in Arokke Hamlet, Liliriattang Village. This research shows that agricultural modernization has brought significant changes to farmers. Changes in the agricultural sector include: (a) an increase in agricultural production. (b) changes in social structure. (c) agricultural modernization also has an impact on the environment. (d) agricultural modernization causes changes in culture and values in society. (e) agricultural modernization has a positive impact on improving the community's economy.